1998
DOI: 10.1115/1.2841382
|View full text |Cite
|
Sign up to set email alerts
|

High-Accuracy Turbine Performance Measurements in Short-Duration Facilities

Abstract: This paper describes work done in preparation for the measurement of stage efficiency in a short-duration shock-tunnel facility. Efficiency measurements in this facility require knowledge of the flow with path pressure and temperature, rotating system moment of inertia, and mass flow. This paper describes in detail and improved temperature compensation technique for the pressure transducers (Kulite) to reduce thermal drift problems, and measurements of the rotating system moment of inertia. The temperature com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The second approach is based on an idea proposed by Haldeman and Dunn [10]. The method consists of performing both an acceleration and deceleration during the same test using a known torque.…”
Section: Methodsmentioning
confidence: 99%
“…The second approach is based on an idea proposed by Haldeman and Dunn [10]. The method consists of performing both an acceleration and deceleration during the same test using a known torque.…”
Section: Methodsmentioning
confidence: 99%
“…Blowdown facilities generally employ some type of brake, which makes measurement of the torque critical. Since the goal of a good performance experiment would be to measure the efficiency using both techniques, an attempt has been made to improve the accuracy of the pressure, moment of inertia, and total temperature measurements in preparation for efficiency experiments This paper reviews the results achieved on the pressure and moment of inertia measurements, and is an abbreviated version of a more detailed report, Haldeman and Dunn (1995). Earlier thermocouple data were reported in Dunn, et al (1990).…”
Section: Introductionmentioning
confidence: 99%
“…In 1991, Halderman et al [9] demonstrated measurements of 0.25% precision within a 95% confidence limit within a transient facility. Whilst other scholars have argued the legitimacy of these results, it is important to note that different facilities require different improvements and data acquisition software to obtain these results.…”
Section: Short Duration Facilities and Characterising Turbine Performmentioning
confidence: 99%
“…Whilst other scholars have argued the legitimacy of these results, it is important to note that different facilities require different improvements and data acquisition software to obtain these results. Nonetheless, over the last 30 years, shortduration facilities have become the clear choice for characterisation of flows to with a high degree of accuracy [9].…”
Section: Short Duration Facilities and Characterising Turbine Performmentioning
confidence: 99%